LEGAL AND REGULATORY FRAMEWORK FOR ORGANIZING EDUCATION FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Meliboyeva Dilrabo Bahodirovna (American Journals, 2024)
This article discusses the legal and regulatory framework for organizing education for children with special educational needs, approaches to the education of children with special educational needs in our country and around the world.
Keywords: Disabled, anomaly, modern approaches, legal framework, inclusive education, integration, rehabilitation, correction.